Changes of Supraspinatus Muscle Volume and Fat Fraction After Successful or Failed Arthroscopic Rotator Cuff Repair. Issue 13 (November 2019) - Wieser, Karl; Joshy, Jethin; Filli, Lukas; Kriechling, Philipp; Sutter, Reto; Fürnstahl, Philipp; Valdivieso, Paola; Wyss, Sabine; Meyer, Dominik C.; Flück, Martin; Gerber, Christian
Background: Muscle atrophy and fatty infiltration are limiting factors for successful rotator cuff (RC) repair. Quantitative data regarding these hallmarks of degenerative muscle changes after RC repair in humans are scarce. By utilizing a new application of the 6-point Dixon magnetic resonance imaging technology, 3-dimensional volume and fat fraction analysis of the whole RC muscle have become possible. Purpose: Quantitative analysis of atrophy and fatty infiltration of the supraspinatus muscle after healed and failed RC tendon-to-bone repair. Study Design: Cohort study; Level of evidence, 3. Methods: Muscle volume and fat fraction were measured preoperatively and at 3 and 12 months postoperatively in 19 failed and 21 healed arthroscopic supraspinatus tendon repairs, with full muscle volume segmentation and magnetic resonance Dixon sequences. Results: In both groups, the muscle volume initially decreased 3 months after RC repair by –3% in intact ( P = .140) and –10% in failed repair ( P = .004) but recovered between 3 and 12 months to 103% ( P = .274) in intact and 92% ( P = .040) in failed repairs when compared with the preoperative volume (difference of change between groups, preoperative to 12 month: P = .013). The supraspinatus muscle's fat fraction did not significantly change after successful repair (6.5% preoperative, 6.6% after 3 months, and 6.7% after 12 months; all nonsignificant). There was, however, a significant increase from 7.8% to 10.8% at 3 months ( P = .014) and 11.4% at 12 months ( P = .020) after failed repair (difference between groups at 3- and 12-month follow-up: P = .018 and P = .001, respectively). Conclusion: After successful arthroscopic repair, RC tendon tear–induced fatty infiltration can be almost stopped, and muscle atrophy can even be slightly reversed. In case of a failed repair, however, these changes are further pronounced during the first 3 postoperative months but seem to stabilize thereafter.